Pengaruh Ukuran Perusahaan, Profitabilitas Dan Pertumbuhan Penjualan Terhadap Tax Avoidance Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019-2021 - Laura Theresia; Dini Hariyanti (Student Research Journal, 2023)
This study aims to examine wether the effect of Company Size, Profitability, and Sales Growth on Tax Avoidance in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX). The method used in this research is associative with a quantitative approach. The population used in this study are 13 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The samples selected based on the purposive sampling method were 7 companies. The data used is secondary data. The collected data were analyzed using the Eviews 9 program. Based on the processed data that has been collected and the results of tests that have been carried out on research, the following conclusions can be drawn: (1) Company size affects tax avoidance (2) Profitability affects tax avoidance (3) Sales growth affects tax avoidance.